Antenatal Infections and Respiratory Outcome in Preterm Infants - Bancalari, Eduardo (American Journal of Perinatology, 2020)
Fetal exposure to infection and inflammation can result in accelerated lung maturation and simultaneously altered lung development. This alteration is characterized by reduced alveolar and vascular formation that is one of the hallmarks of the changes observed in animal models and in infants with bronchopulmonary dysplasia (BPD). These opposite effects on maturation and on lung development can explain the reduced severity of respiratory distress syndrome (RDS) but increased incidence of BPD observed in infants exposed to antenatal infections. This also explains why infants born to mothers with chorioamnionitis or colonized with ureaplasma urealitycum have an increased risk of lung injury and BPD. Despite the negative effects of infection on lung development, there is no clear evidence that antibiotic therapy improves the respiratory course in these infants. While the administration of azithromycin to ureaplasma colonized infants is effective in eradicating airway colonization, the effect on BPD is inconclusive. One of the few interventions that have been shown to improve respiratory outcome and reduce BPD in infants with severe RDS is the modulation of inflammation by the administration of systemic or intratracheal steroids early after birth.Key Points
Keywords: prematurity; lung development; chorioamnionitis; bronchopulmonary dysplasia